Evaluation of the Economic Burden of Diseases Associated With Poor Nutrition Status. (6th December 2013) - Cangelosi, Michael J.; Rodday, Angie Mae; Saunders, Tully; Cohen, Joshua T.
Abstract : Background: Geriatric acutely ill patients may frequently have insufficient nutrition intake, leading to malnutrition and increased susceptibility to additional morbidity. This compromised health status can increase costs by extending length of stay in the hospital, promoting the development of comorbidities, and requiring more intensive care. Understanding the value of measures improving the health of these patients depends in part on estimating the costs of prevented adverse outcomes. Because clinical trials often do not record these costs, it is difficult to assess the value of nutrition interventions. Materials and Methods : This article comprehensively reviews 15 years of clinical trials of nutrition interventions to identify salient diseases and complications measured by previous clinical trials and then estimates costs corresponding with these conditions associated with poor nutrition status. Results : The most costly complication associated with poor nutrition status is acute respiratory infections ($13, 350–$19, 530 per hospitalization), while institutional long‐term care is the greatest chronic cost contributor across many diseases ($77, 000 per year of care). Conclusion : This review can facilitate imputation of nutrition intervention benefits for acutely ill patients by characterizing the costs of clinical outcomes often reported in trials.